Growth and isoenzyme comparison of five isolates of Venturia inaequalis - Roig, E.; Neumann, P.; Simon, J.-P. (Phytoprotection, 1990)
Observation of the mycelial aspect of five isolates representing the fîve races of Venturia inaequalis indicates that it is possible to differentiate these isolates by their growth pattern and the isolate of race 3 appears to be the most easily distinguishable. Fifteen enzyme systems and non-specific proteins have been analyzed by polyacrylamide and starch gel electrophoresis. Thirteen of the isoenzymes systems and non-specific proteins showed no variation among the five isolates. Esterases isoenzyme patterns allow separation of the isolates since only one isoenzyme is common to all isolates and two others are shared by isolates of race 1 and 5. One carbonic anhydrase isoenzyme was observed to be specific to the isolate of race 2.